Factors Influencing Stunting among Children Aged 0–59 Months - Nila Sari; Johanna Christy (Indonesian Journal of Global Health Research, 2025)
Stunting is a condition characterized by impaired growth and development in children under five, caused by chronic nutritional deficiencies, resulting in a child being too short for their age. Objective to identify the factors associated with the incidence of stunting among children under five in West Nias Regency. This study was an analytical observational research with a case-control design conducted in West Nias Regency. The sample consisted of 25 children under five in the case group and 25 children in the control group, selected using purposive sampling. Data were collected using questionnaire and analyzed using the Chi-square test, and cross-tabulation was employed to assess the strength of the association between variables by examining the Odds Ratio (OR) values. The study showed that energy adequacy (OR = 8.333; CI = 2.280–38.762), protein adequacy (OR = 8.000; CI = 1.839–38.175), maternal knowledge (OR = 8.000; CI = 1.839–38.175), maternal education (OR = 23.677; CI = 4.385–118.568), and family income (OR = 14.222; CI = 2.690–61.680) were identified as risk factors for stunting. In contrast, other variables in this study, including low birth weight (OR = 1.678; CI = 0.346–10.604), breastfeeding history (OR = 0.463; CI = 0.35–5.988), and maternal occupation (OR = 1.356; CI = 0.563–4.64), were not found to be significant risk factors for stunting. Inadequate energy and protein intake, limited maternal knowledge, low maternal education, and low family income are risk factors for stunting among children aged 0–59 months.